1981
DOI: 10.1038/289491a0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the phagocytosis-inducing IgG-binding antigen on senescent somatic cells

Abstract: To remove senescent red blood cells (RBCs) from the circulation, macrophages must distinguish them from mature RBCs. That is achieved by a specific recognition system. An antigen that develops on the surface of a senescing RBC is recognized and bound by the Fab region of an IgG autoantibody in the serum. Subsequently the Fc region of the autoantibody is recognized and bound by a macrophage, which proceeds to phagocytose the RBC. The antigenic molecule can be extracted from senescent but not young RBCs with Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
135
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 10 publications
5
135
0
1
Order By: Relevance
“…Although the senescent-cell antigen was first demonstrated on the surface of senescent human erythrocytes (1,2), it has since been demonstrated on the surface of lymphocytes, polymorphonuclear leukocytes, platelets, embryonic kidney cells, and adult liver cells (5). A molecule immunologically related to band 3, the molecule from which senescent-cell antigen is derived, has been observed on all cells examined (28,29).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Although the senescent-cell antigen was first demonstrated on the surface of senescent human erythrocytes (1,2), it has since been demonstrated on the surface of lymphocytes, polymorphonuclear leukocytes, platelets, embryonic kidney cells, and adult liver cells (5). A molecule immunologically related to band 3, the molecule from which senescent-cell antigen is derived, has been observed on all cells examined (28,29).…”
mentioning
confidence: 99%
“…The "neo-antigen" is recognized by the antigen binding, Fab, region (3,10,11) of a specific IgG autoantibody in serum that attaches to it and initiates the removal of cells by macrophages (1)(2)(3)(4). A number of studies performed by us (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and by others have demonstrated the presence of IgG on senescent, damaged, and stored erythrocytes (12)(13)(14)(15)(16)(17)(18)(19)(20)1). In addition, workers in several laboratories have recently presented evidence that IgG binding is also involved in the removal of erythrocytes in diseases such as thalassemia (21) and sickle cell anemia (22,23).…”
mentioning
confidence: 99%
See 3 more Smart Citations